Factors associated with nonachievement of low density lipoprotein cholesterol target among patients with type 2 diabetes mellitus - Mat Yudin, Zainab (2015)

(untitled)
Introduction: Dyslipidaemia is a risk factor for cardiovascular disease and Type 2 Diabetes Mellitus is a cardiovascular risk equivalent. Low density lipoprotein cholesterol (LDL-C) is the primary target in the management of dyslipidaemia and achievement of LDL-C target according to National Cholesterol Education Programme (NCEP-ATP III) is crucial. Statins are potents drug to reduce cholesterol especially the LDL-C, however the effectiveness is limited by the poor adherence. Objectives: To determine proportion of patients achieve LDL-C target and factors associated with nonachievers and the adherence to statin therapy among patients with T2DM. Methodology: A cross sectional study involving 234 patients aged 18 years old and above who had comorbid Type 2 Diabetes Mellitus and Dyslipidaemia. Systematic Random Sampling with replacement method was applied to select participants who attended KRK, HUSM from January 2013 to May 2013. Both self-administered and interviewered administered questionnaires were used to obtain the socio demographic characteristics, clinical characteristics and compliance questionnaire. The data was analysed for descriptive statistic and multiple logistic regression. Result: The percentage of LDL-C target achievement was 37.6%. The percentage of patients adhered to statin therapy was 98.3% and 20.5% of patients adhered fully. There was no significant relation between LDL-C achievement and adherence. Sociodemographic data(such as age, marital status, gender, education level and household income) and clinical data (such as smoking status, number of prescribed medications, BMI, SBP, duration on statin therapy and type of statin taken) were not associated with achievement of LDL-C target. HbA1c is the only significant factor that associated with LDL-C target achievement. Conclusion: Achievement of LDL-C target among T2DM patients attended KRK,HUSM was still low. Majority patients were adhered to statin therapy however the relation between adherence and LDL-C achievement was not significant. HbA1c was the only significant factor associated to nonachievement of LDL-C target. Patients with poorly control glycaemic control should more holistically manage including achieving their LDL-C target.